The influence of Ramadan on physical performance measures in young Muslim footballers - Kirkendall, D. T.; Leiper, J. B.; Bartagi, Z.; Dvorak, J.; Zerguini, Y. (Journal of Sports Sciences, 2008)
Ramadan alters the normal patterns of food intake and sleep. The aim of this study was to describe the impact of Ramadan on physical performance in youth Muslim athletes. The members of four Tunisian teams (age 18 years, N = 85) resided at the Tunisian Football Federation training ground. Each player chose either to fast or not fast during the 4-week period of Ramadan. Two teams were randomly chosen for morning testing; the remaining teams were tested in the afternoon. Testing took place 3 weeks before and in the second and fourth weeks of Ramadan. A subgroup of 45 players was tested again 3 weeks after Ramadan. Each player was assessed for speed, power, agility, endurance, and for passing and dribbling skills. No variables were negatively affected by fasting. Almost all variables had improved significantly by the third test session (training effect). A limited number of variables were also significant for time of day or in an interaction with week of testing. Changes in performance were most likely due to the effects of training and familiarity with the test methods. Based on these data, Ramadan had little effect on objective tests of physical performance in this sample of youth players observing Ramadan.